Nowe możliwości i stare ograniczenia. Priorytety polskiej polityki zagranicznej 2012-2016 w kontekście dziesiątej rocznicy akcesji Polski do Unii Europejskiej - Mróz, Maciej (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2014)
The author proves that a high level of vagueness and lack of consistency in the document titled: Priorytety polskiej polityki zagranicznej na lata 2012–2016 (Priorities of Poland’s foreign policy for 2012–2016), as well as lack of emphasis on the issues crucial for the Poland’s raison d’etat both in the national and state-national dimension, preeminently resulted from the fact that it addressed a wide range of public opinion in the country itself and abroad, which in principle imposed the way of presenting the fundamental principles of Poland’s foreign policy. Nevertheless, the first two priorities outlined in the governmental document Priorytety polskiej polityki zagranicznej 2012-2016, including strategies within the European Union, i.e. strong Poland in a strong political union and Poland as a reliable ally in a stable Euroatlantic order, will probably remain an essential and indisputable indicator of international activity of the Third Republic of Poland for years to come
Keywords: polska polityka zagraniczna; Racja Stanu; obszar euroatlantycki; priorytety polityczne; NATO; bezpieczeństwo; Unia Europejska; interesy; dyplomacja